STRATEGI PEMASARAN BERBASIS ANALISIS KEKUATAN, KELEMAHAN, PELUANG, DAN ANCAMAN USAHA PERHOTELAN DI DALEM AGUNG PALAGAN - Heni Widyaningsih; T. Prasetyo Hadi Atmoko (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2015)
ABSTRACT Yogyakarta is one area that has great potential in the field of tourism. Availability of facilities and supporting infrastructure such as hotels, restaurants, travel agencies and others, making tourist visits increased to Daerah Istimewa Yogyakarta. The number of hotels that stand in Yogyakarta making hospitality business competition is getting tougher. Dalem Agung Palagan is one of the hotels in Yogyakarta, which has its own uniqueness in concept building and its facilities.The purpose of this study was to determine Based Marketing Strategy Analysis of Strengths, Weaknesses, Opportunities and Threats Hospitality businesses in Dalem Agung Palagan. This study used a descriptive analytical method is translation, followed by an analysis based on facts and data that has been collected. The results of this study are professional resources are factors internal forces that are the hallmark of Dalem Agung Palagan. lack of knowledge and limited menu provided a weakness Dalem Agung Palagan, environment and cultural traditions of Javanese palace is an opportunity for the Great Hotel. Natural disasters such as the eruption of Mount Merapi threats to Dalem Agung Palagan for tourists to be afraid to visit Yogyakarta. Strategy undertaken by Dalem Agung Palagan to achieve success is through product marketing, distribution, promotion and Networking. Keywords: Marketing, Strengths, Weaknesses, Opportunities, and Threats